Clinicopathological Study of Duodenal Gastrointestinal Stromal Tumors (GIST) - Ali Shan Ismail, Karim Bux, Sandesh Kumar, Muhammad Rashid Naveed, Hammad Ahmed Butt, Alfarah Rehmat Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Tumors of the gastrointestinal tract (GIST) are the most commonly seen tumors of the gut. The current study aimed to evaluate the clinical and pathological features of gastrointestinal stromal tumors presented in our setting. Methodology: A prospective observational study was conducted at a tertiary care center, Pakistan between January 2019 to March 2021. All cases of duodenal and stomach gastrointestinal stromal tumors diagnosed and treated at our center were analyzed in our study. All clinicopathological tumors including patient characteristics, treatments, histological examinations, and Genomic mutation were documented. The clinicopathologic parameters were compared between stomach and duodenal GIST. Results: A total of 221 patients were enrolled in the study. The majority were below the age of sixty years. The male to female ratio was 0.97. The most common presenting symptom was active bleeding or severe anemia with a frequency of 114 (51.6%). The majority of the duodenal GIST were present in the descending portion. 147 (66.5%) patients were offered limited resection while 25.8% were offered pancreaticoduodenectomy, and the remainder were not operated. About 30 (13.6%) patients had genetic mutation. Of these, the majority had a KIT mutation. In four patients, KIT and PDGFRA were both mutated. We stratified the patients with respect to the clinicopathological factors and found that tumor size was significantly associated with duodenal GIST (p<0.001). Tumor size of > 10 cm was more frequently found in duodenum than stomach >10 [26 (11.8%) vs. 21 (6.7%)]. Conclusion: The present study highlights the clinicopathological pattern of GIST in our population. Furthermore, it indicated that the tumor size was significantly greater in patients diagnosed with duodenal GIST as compared to stomach GIST.